Toward a neuromorphic microphone - Smith, Leslie S. (Frontiers in Neuroscience, 2015)
Neuromorphic systems are used in variety of circumstances: as parts of sensory systems, for modelling parts of neural systems and for analog signal processing. In the sensory processing domain, neuromorphic systems can be considered in three parts: pre-transduction processing, transduction itself and post-transduction processing. Neuromorphic systems include transducers for light, odours and touch but so far neuromorphic applications in the sound domain have used standard microphones for transduction. We discuss why this is the case and describe what research has been done on neuromorphic approaches to transduction. We make a case for a change of direction towards systems where sound transduction itself has a neuromorphic component.